The Application of TPACK for Teaching Content Courses: Process, Students' View, and Product in Indonesian Context - Lestari Setyowati; Sri Rachmajanti (Journal of Innovation in Educational and Cultural Research, 2023)
Due to the pandemic breakout in 2020, all facets of human life have been subject to unexpected changes. To sustain learning activities, many educational institutions have utilized Technological Pedagogical Content Knowledge (TPACK) as way-outs. It is true for delivering content courses at the English Department, Faculty of Letters, State University of Malang, East Java, Indonesia. One affected course is teaching English for Young Learners (EYL) for sixth-semester students. Thus, this article aims to describe the implementation of TPACK, the students' view, and the product results from the process. The design of this study is an exploratory sequential design. The participants were twenty-one Offering C students taking the EYL course. Thus, data were collected qualitatively (classroom observations, semi-structured interviews, video watching, mid and final-term assessments) and quantitatively (the Likert scale questionnaire). The findings reveal that: 1) the process of teaching EYL courses TPACK involved flipped learning in the initial meeting followed by a discussion session, and the technology used was Google meet, Google class, YouTube, WhatsApp, and technical tools like a tutorial video for media demonstration, and video making; 2) the students agree on the use of technology for their learning of EYL course and feel that they have had a lot to learn from TPACK for their course, and 3) the products generated from the teaching-learning process are video and intellectual rights certificates (HKI).